The Effect of Accounting Information Systems and Internal Control on the Sales Performance of MSMEs in Sungai Penuh City - Putri, Nurapni Jami (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to analyze the influence of Accounting Information Systems (AIS) and Internal Control on the sales levels of Micro, Small, and Medium Enterprises (MSMEs) in Sungai Penuh City. The background of this research is based on the importance of implementing effective AIS and internal control in supporting operational activities and achieving sales performance among MSMEs amid increasingly competitive business conditions. This research uses a quantitative approach, in which data were collected through the distribution of Likert-scale questionnaires to MSME practitioners. The population includes all MSMEs operating in Sungai Penuh City, with samples selected using purposive sampling based on specific criteria such as business duration, business scale, and the use of information systems in transaction recording. The data analysis technique employed is multiple linear regression to examine both the simultaneous and partial effects of the independent variables on the dependent variable. The results show that, partially, the Accounting Information System has a positive and significant effect on the sales level of MSMEs in Sungai Penuh City. Meanwhile, Internal Control does not have a significant effect on sales levels. However, simultaneously, Accounting Information Systems and Internal Control have a significant effect on sales performance. These findings highlight the importance of implementing a well-structured accounting information system to support improved sales performance, as well as the need for the development of a more organized internal control system within the MSME sector.